Stress Corrosion Cracking in Sea Water of a Steel for Offshore Applications - PASTORE, Tommaso (ASME, 1987)
In this work the stress corrosion cracking of an API 5L X65 steel was studied by means of the Slow Strain Rate technique utilizing precracked specimens. Tests showed a noticeable effect of the environmental conditions on the hydrogen embrittlement behaviour of the material. Some useful parameters obtainable with this technique are also discussed.